Carbon-nitrogen bond-forming reactions of dialkyl azodicarboxylate: a promising synthetic strategy - Nair, Vijay; Biju, Akkattu T.; Mathew, Smitha C.; Pattoorpadi, Beneesh Babu (Chemistry an Asian Journal, 2008)
Azodicarboxylates have found applications in electrophilic amination reactions and in pericyclic reactions. The nucleophilic trigger in Mitsunobu reactions, that is, the zwitterion formed from triphenylphosphine and dialkyl azodicarboxylate, has been utilized recently in various heterocyclic constructions. This Focus Review summarizes the potential utility of azodicarboxylates in various carbon–nitrogen bond-forming reactions.
Keywords: amination reactions; azodicarboxylates; C[BOND]N bond formation; heterocycles; Huisgen zwitterion